2014
DOI: 10.1371/journal.pone.0088134
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Oxacillin-Susceptible mecA-Positive Staphylococcus aureus (OS-MRSA) Associated with Bovine Mastitis in China

Abstract: Staphylococcus aureus is a main cause of bovine mastitis and a major pathogen affecting human health. The emergence and spread of methicillin-resistant Staphylococcus aureus (MRSA) has become a significant concern for both animal health and public health. This study investigated the incidence of MRSA in milk samples collected from dairy cows with clinical mastitis and characterized the MRSA isolates using antimicrobial susceptibility tests and genetic typing methods. In total, 103 S. aureus isolates were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 37 publications
7
76
2
2
Order By: Relevance
“…Therefore, the findings of the strains with MLST and spa type known in human infection in the current study may point towards transmission between human to animals. We also found pvl positive isolates, which are rarely reported in animal origin strains [8]-[10]. The pvl gene is also a virulence factor that is mainly associated with community acquired-MRSA (CA-MRSA) infections that causes serious pathology including skin infections and necrotizing pneumonia in humans [4648].…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the findings of the strains with MLST and spa type known in human infection in the current study may point towards transmission between human to animals. We also found pvl positive isolates, which are rarely reported in animal origin strains [8]-[10]. The pvl gene is also a virulence factor that is mainly associated with community acquired-MRSA (CA-MRSA) infections that causes serious pathology including skin infections and necrotizing pneumonia in humans [4648].…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies suggested that amino acid mutations in the Fem proteins (involved in cell wall synthesis) might lead to the oxacillin-sensitive methicillin-resistant staphylococcus phenotype, but the association of mutations with the phenotype has not been formally proven (Giannouli et al 2010;Pu et al 2014). Furthermore, Fem genes that encode proteins which considerably affect the level of methicillin resistance were suggested to be specific only for Stahylococcus aureus (Kobayashi et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…que se caracteriza pela forma subclínica da infecção, com elevação na quantidade de células somáticas (>200.000 céls/mL). Entretanto há relatos da manifestação clínica da doença, ocasionada por MRS, nesses casos os animais apresentam um quadro agudo da infecção, onde são observadas alterações macroscópicas no leite, no tecido mamário e sistêmicas no animal (Chandrasekaran et al 2014a, Pu et al 2014, Lim et al 2013, Vanderhaeghen et al 2010.…”
Section: Staphylococcus Spp Resistente à Meticilina Em Casos De Masunclassified